Analytical Study of Physical Fitness Components for Football Juniors in Some Clubs in DhiQar Governorate - Ali Hussein Ali Al-Saeedi (Penerbit Jurnal Indonesia, 2025)
Purpose of physically training adolescents in sports clubs is to get them ready for physical and technical effort by boosting their physical and psychological levels. Modern football is a game that takes a significant deal of physical effort and fitness, thus it has become vital to train youngsters physically throughout the preparation and formation stage, since this is the basic stage that prepares the player physically for matches and tournaments. Thus, the research problem is defined in